Cashier and stock management module of shop management system - Mah, Wen Sian (2010)
Some of the small clothing stores or boutique shops are using different system to running different business activities. There some problems that cause management not efficiency handled. Computer technology is emerged as new force to substitute traditional management method. Shop Management System (SMS) is a software application to be developed to manage most of the activities or tasks running in a boutique shop. This system has divided to three main modules that are cashier and stock management, supplier information management and generating report, and fingerprint authentication and staff management. The module developed by myself is Cashier and Stock Management (CSM). SMS is the combination of these features together in one system to managing the shop activities which are much easier than using different kind of applications which may costly, wasting time and inefficient. This thesis shall explain detail development process and related information such as introduction, literature reviews, methodology, implementation, result and discussion and conclusion of CSM with supported documents of Software Development Plan, Software Requirement Specification, Software Design Document and Software Test Design.